Role of the nuclear membrane protein Emerin in front-rear polarity of the nucleus - Paulina Nastały; Divya Purushothaman; Stefano Marchesi; Alessandro Poli; Tobias Lendenmann; Gururaj Rao Kidiyoor; Galina V. Beznoussenko; Stefania Lavore; Orso Maria Romano; Dimos Poulikakos; Marco Cosentino Lagomarsino; Alexander A. Mirоnоv; et al. (2020)
Abstract Cell polarity refers to the intrinsic asymmetry of cells, including the orientation of the cytoskeleton. It affects cell shape and structure as well as the distribution of proteins and organelles. In migratory cells, front-rear polarity is essential and dictates movement direction. While the link between the cytoskeleton and nucleus is well-studied, we aim to investigate if front-rear polarity can be transmitted to the nucleus. We show that the knock-down of emerin, an integral protein of the nuclear envelope, abolishes preferential localization of several nuclear proteins. We propose that the frontally biased localization of the endoplasmic reticulum, through which emerin reaches the nuclear envelope, is sufficient to generate its observed bias. In primary emerin-deficient myoblasts, its expression partially rescues the polarity of the nucleus. Our results demonstrate that front-rear cell polarity is transmitted to the nucleus and that emerin is an important determinant of nuclear polarity.